The Influence Of Financial Literacy And Ease Of Use Of The Qris System On Students’ Decisions In Using Qris - Wulandari, Sri Winda; Ramadhan, Zulfikar (Universitas Bangka Belitung, 2025)
The purpose of this study is to determine the influence of financial literacy and usefulness on students' decisions in using QRIS. This research is an associative research using a quantitative approach. The purposive sampling technique is used for sampling. The calculation of the total sample using the Lemeshow formula with an error of 5% resulted in the results of 96 samples. The data collection tool used is a questionnaire that is distributed and filled out by a sample, namely FEB students of the 2021, 2022, 2023, and 2024 batches of the University of Muhammadiyah Jakarta. Data processing was carried out using the SPSS 20 application and validity and reliability tests were used to test the instrument. We then performed a normality test, a multicollinearity test, and a heteroscedasticity test to test the classical assumptions. The data analysis methods used include multiple regression analysis, T test, F test, and determination coefficient (R2) test. The results of this study show that financial literacy and ease of use of the QRIS system have a positive and significant effect on students' decisions in using QRIS.